Structural and ultrastructural changes during the infection of UFL-AG-286 cells with the baculovirus AgMNPV - Pombo, Vivian (1998)
During infection of the permissive insect cell line UFL-AG-286 by the baculovirus Anticarsia gemmatalis nucleopolyhedrovirus (AgMNPV-2D) several morphological changes occur. By 12 h postinfection (h p.i.), the infected cells became round and exhibited a decrease in the number of cytoplasmic projections. By 24 h p.i., it was possible to detect a virogenic stroma inside the cell nucleus, and after 48 h p.i., polyhedral inclusion bodies were observed. Some of these morphological modifications are probably due to changes in the cytoskeleton of the cell and this possibility was substantiated by the observation that the distribution of actin and microtubules was dramatically modified upon infection. Several viral-induced proteins were also produced during infection and a sharp decrease in overall protein synthesis was observed. These results are very similar to those obtained with other cell lines infected with different baculoviruses, indicating a similar mechanism of infection.